The Relationship Between Protein and Iodine Intake and The Incidence of Stunting in Toddlers Aged 12-24 Months at The Srumbung Health Center, Magelang Regency - Sulistyani, Theresia Deby; Setyaji, Diyan Yunanto; Purnawijayanti, Hiasinta Anatasia (Journal of Global Nutrition, 2024)
Stunting is a condition of growth failure in toddlers due to chronic malnutrition, especially in the first 1000 days of life, namely from when the child is in the womb until the age of 24 months. Toddlers are said to be stunted if their height per age is <-2 SD. The purpose of this study was to determine the relationship between protein intake and iodine intake with the incidence of stunting in toddlers aged 12-24 months at the Srumbung Health Center, Magelang. This study used a cross-sectional research design with a sample size of 100 toddlers aged 12-24 months at the Srumbung Health Center. Based on the results of the study, it was stated that the better the daily protein intake of toddlers in the last 3 months, the lower the risk of toddlers aged 12-24 months at the Srumbung Health Center experiencing stunting. From this study, it can be concluded that the incidence of stunting in toddlers aged 12-24 months in the Srumbung Health Center area is related to protein intake but not to iodine intake.